LDPC error correction for QKD - Tan, Xin Long. (2013)
Quantum key distribution (QKD) system uses quantum cryptography to provide a means of secured communication. Key distillation which is a key component of the QKD system involves information reconciliation (IR). IR is used to ensure the keys used by Alice and Bob are identical. Popular methods such as Cascade have been used traditionally in the IR process, however, the heavy interactions between Alice and Bob poise a problem of revealing too much bits[1]. In this project, we aim to study using Low-Density Parity-Check codes for error correction in the IR process. The performances of LDPC codes with different decoding algorithm under various channel conditions will also be studied. This project will be using Binary Symmetrical Channel (BSC) in the studies and simulation. A method to improve the codes performance significantly is proposed in the project.